Implicit Emotion Regulation Deficits in Trait Anxiety: An ERP Study - Liu, Bingqian; Wang, Yi; Li, Xuebing (Frontiers in Human Neuroscience, 2018)
According to the framework of emotion regulation (ER), both explicit and implicit forms are essential to well-being. It is the interaction between these two processes that ensures adaptive emotional responses. Although many studies have focused on explicit ER deficits in anxiety, there is still a lack of awareness about the implicit form and its role in anxiety. To address this issue, we explored the time course of implicit ER processes in individuals with high and low trait anxiety. To do this, we employed the newly developed PI (Priming-Identify) paradigm, which includes a word matching task (externally-generated implicit goals) and a facial expression identify task (emotion processing). We aimed to modulate the implicit ER goals of individuals through the application of different priming conditions (ER-related and -unrelated words). In addition to their behavioral effect, we recorded the influence of these priming conditions through event-related potentials (ERP) during the facial expression identify task. Three ERP components were chosen as indexes of three stages of implicit ER processing: N170, early posterior negativity (EPN) and late positive potential (LPP). In individuals with low trait anxiety (LTA), the early N170 and the middle EPN were enlarged under the ER-related priming condition, while the late positive potential (LPP) was not influenced. However, in individuals with high trait anxiety (HTA), we observed an absence of any significant differences between the ER-related and -unrelated priming conditions across all three ERP components. Furthermore, enlargements of N170 and EPN amplitudes were significantly correlated with a decrease in negative emotion experience scores. Our results suggest that HTA individuals experience implicit ER deficits occurring during the early and middle stages of the regulation of emotion.